WAIS Divide Multi Track Electrical Measurements - Fudge, T. J.; Taylor, Kendrick C. (IEDA: US Antarctic Program Data Center, 2019)
Images of the multi-track electrical data for depths below 1956 m are given in mt_compiled_1958_3406.pdf. Images are approximately to scale. Data for individual sections can be obtained by contacting T.J. Fudge at tjfudge@uw.edu. Warm colors are high electrical conductivity. Cool colors are low electrical conductivity. Each track is normalized by subtracting the mean and dividing by the standard deviation. Plotted values are a 3-measurement (3mm) running average. Measurements affected by breaks in the core have been masked out. X-axis is approximate horizontal position on the ice core, as measured from left from looking from bottom to top of the core. Y-axis is depth in meters. Title is the tube number.